A Form of Hope in Richard Strauss's Metamorphosen. (28th May 2021) - TAN, EMILY X. X.
ABSTRACT: Richard Strauss's Metamorphosen was composed in the final months of the Second World War and is often described as the composer's personal elegy for the decline of Western culture. This article presents a new reading of the work which challenges the pessimistic interpretations currently surrounding it. I argue that sonata form and its associated hermeneutic narratives fail to account fully for its structure and suggest instead that Strauss's negotiation and eventual surpassing of this paradigmatic tonal form offers a deeper insight into its meaning. Drawing an analogy between the autonomous musical work and sonata structure on the one hand, and the modern human subject and social ideology on the other, I posit that, as Metamorphosen aims towards the production of a new sense of totality, so the subject finds meaning beyond the ideological limitations of its circumstance.